Decreased in Liver Fibrosis in Patients with HCV/HIV Coinfection After Treatment with Sofosbuvir/Daclatasvir - Andreas Jonathan; Rudi Wisaksana; Nenny Agustanti (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Background: Hepatitis C Virus (HCV)/Human Immunodeficiency Virus (HIV) co-infection increases the progression of liver fibrosis to advanced liver disease and death. The aim of this study is to determine whether decreased of liver fibrosis occur in HCV/HIV coinfection patients after therapy with Sofosbuvir/daclatasvir. Method: This study used a quasi-experimental study design without a control group. The study subjects were HCV/HIV coinfection patients who received Sofosbuvir / daclatasvir therapy in the Gastroentero-Hepatology Clinic of Dr. Hasan Sadikin Hospital. In this study measurement of liver fibrosis was carried out by using AST to Platelet Ratio Index (APRI) and Fibrosis-4 Index (FIB-4) before therapy and when SVR-24 was achieved.Results: The study involved 29 subjects. Most of the research subjects were men, with an average age of 40.38 years (SD 3.48). From the results of this study, we found a decrease in APRI scores and FIB-4 index when HCV / HIV coinfection patients, that were treated with Sofosbuvir/ Daclatasvir, achieved SVR 24. The median of APRI scores before therapy and after SVR-24 was decreased from 0.41 to 0.28 (95% CI: 0.01 - 0.23, p-value 0,01) and the median of FIB-4 Index before therapy and after the SVR 24 was decreased from 0.94 to 0.81 (95% CI: -0, 04 - 0.35, p-value 0.28).Conclusion: This study concluded that therapy using Sofosbuvir / Daclatasvir in HCV / HIV coinfected patients has very good effectiveness and can reduce liver fibrosis.